THE EFFECT OF TECHNOLOGY-BASED LEARNING MEDIA ON ARABIC LEARNING OUTCOMES AMONG STUDENTS AT AL KAUTSAR AL AKBAR ISLAMIC BOARDING SCHOOL IN MEDAN - Nissa Zahra Silmy Damanik; Yahfizham Yahfizham (Yayasan Haiah Nusratul Islam, 2025)
This study aims to determine the effect of technology-based learning media on Arabic learning outcomes in students. In the digital era, the use of technology in the learning process has become an important strategy to improve the effectiveness and attractiveness of learning. Arabic, as a subject that requires a deep understanding of vocabulary, grammar, and language skills, is greatly assisted by the presence of interactive and flexible technological media. Through a quantitative approach, data was collected from students who used technology-based media in Arabic language learning and analyzed to assess the extent of improvement in their learning outcomes. The results of the study indicate that the use of technology-based media has a significant impact on improving students' learning outcomes, particularly in terms of material comprehension and learning motivation. Therefore, the use of technology-based learning media is recommended as part of the teaching strategy for Arabic language instruction in schools.